(untitled) (Islamic Sciences Journal, 2023)
The guidance of immigrants and supporters is the practical translation of the principles and morals of Islam, which they derived from the life of the Messenger of God, which is the actual application of his law and curriculum. God supported him with immigrants and supporters to be the best role model that ordered us to follow them and weaving in their lines, because the qualities of goodness gathered among them, and each of them was a Quran walking on earth .Therefore, the nation has not raised before or after, and the individual or society is not built except by jurisprudence of their guidance, and looking for a mechanism to activate their approach in our reality. With these good qualities, the first generation has risen and achieved sovereignty and leadership. The individual, society and the Muslim nation today will not achieve its renaissance and leadership.